The Influence of Artificial Intelligence-Driven Marketing on the Competitiveness of Agricultural Products in the Digital Economy - Malta (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2026)
The rapid development of the digital economy has transformed agricultural product marketing from conventional approaches into technology-driven strategies that emphasize data utilization and digital platforms to strengthen market competitiveness. Increasing competition in digital markets requires agricultural businesses to adopt more adaptive marketing strategies capable of responding to changing consumer preferences, expanding market reach, and improving marketing performance. In this context, Artificial Intelligence has emerged as a strategic enabler for optimizing marketing activities by supporting data-driven decision-making, enhancing promotional effectiveness, and improving communication with consumers. This study aims to analyze the role of Artificial Intelligence-driven marketing in enhancing the competitiveness of agricultural products in the digital economy. This study employed a qualitative approach using a literature review method by analyzing relevant books, scientific articles, and previous studies, with the collected data being systematically interpreted and synthesized to address the research objectives. The findings indicate that Artificial Intelligence-driven marketing contributes to improving the competitiveness of agricultural products by expanding market reach, increasing product value, strengthening consumer engagement, and enhancing overall marketing performance. The effectiveness of its implementation is supported by digital infrastructure readiness, high-quality marketing data, competent human resources, organizational support, and the integration of technology into marketing activities, although several implementation challenges remain. Therefore, strengthening adaptive marketing strategies, fostering technological innovation, encouraging stakeholder collaboration, and developing market-oriented digital marketing initiatives are essential to achieving sustainable competitiveness of agricultural products in the digital economy.